Neutrino transport in coherent quasiparticle approximation - Ilmavirta, Joonas (2012)
We introduce the coherent quasiparticle approximation (cQPA), a model in thermal quantum field theory which describes various effects of temporally varying thermal medium on particle propagation. We present the cQPA Feynman rules and develop related calculational tools. Using these methods we calculate neutrino self energies in the Standard Model and derive an equation of motion for neutrino propagation in a very general framework. Some immediate implications of this equation are discussed. (More detailed abstract in the PDF file.)